Nightmare alley - Gresham, William Lindsay 1909-1962; Mockridge, Cyril J. 1896-1979 (The Criterion Collection, 2021)
"Darkness lurks behind the bright lights of a traveling carnival in one of the most haunting and perverse film noirs of the 1940s. Adapted from the scandalous best seller by William Lindsay Gresham, Nightmare Alley gave Tyrone Power a chance to subvert his matinee-idol image with a ruthless performance as Stanton Carlisle, a small-time carny whose unctuous charm propels him to fame as a charlatan spiritualist, but whose unchecked ambition leads him down a path of moral degradation and self-destruction. Although its strange, sordid atmosphere shocked contemporary audiences, this long-difficult-to-see reflection of postwar angst has now taken its place as one of the defining noirs of its era-a fatalistic downward slide into existential oblivion." [criterion.com]
Original: USA 1947
DVD special edition features: new 4K digital restoration ; audio commentary from 2005 featuring film historians James Ursini and Alain Silver ; new interview with critic Imogen Sara Smith ; new interview with performer and historian Todd Robbins ; interview from 2007 with actor Coleen Gray ; audio excerpt from a 1971 interview with Henry King in which the filmmaker discusses actor Tyrone Power ; trailer ; English subtitles for the deaf and hard of hearing ; plus: An essay by film writer and screenwriter Kim Morgan
Bildformat 1.37:1
Keywords: Film; DVD-Video